Le premesse filosofiche dell'antitotalitarismo e dell'antinihilismo politico di Cornelio Fabro - Castellano, Danilo (Sapientia, 2006)
This contribution considers the theoretical premises of Cornelio Fabro's political thought. In particular, it deals with the issue of the (human) subject, which is a central concern for modern and, especially, contemporary philosophy: against all the doctrines which reduce the subject to an "event", Cornelio Fabro takes it to be a given "identity", always identical on the ontic level, and always new on the moral level. This contribution shows that Fabro's interest for this issue originated from dramatic events (the second world war), which represented problems for the both individual and the collective experiences, and, which hence became a philosophical question for our time.